An optimised protocol for molecular identification of Eimeria from chickens() - Kumar, Saroj (Elsevier, 2014)
Molecular approaches supporting identification of Eimeria parasites infecting chickens have been available for more than 20 years, although they have largely failed to replace traditional measures such as microscopy and pathology. Limitations of microscopy-led diagnostics, including a requirement for specialist parasitological expertise and low sample throughput, are yet to be outweighed by the difficulties associated with accessing genomic DNA from environmental Eimeria samples. A key step towards the use of Eimeria species-specific PCR as a sensitive and reproducible discriminatory tool for use in the field is the production of a standardised protocol that includes sample collection and DNA template preparation, as well as primer selection from the numerous PCR assays now published. Such a protocol will facilitate development of valuable epidemiological datasets which may be easily compared between studies and laboratories. The outcome of an optimisation process undertaken in laboratories in India and the UK is described here, identifying four steps. First, samples were collected into a 2% (w/v) potassium dichromate solution. Second, oocysts were enriched by flotation in saturated saline. Third, genomic DNA was extracted using a QIAamp DNA Stool mini kit protocol including a mechanical homogenisation step. Finally, nested PCR was carried out using previously published primers targeting the internal transcribed spacer region 1 (ITS-1). Alternative methods tested included sample processing in the presence of faecal material, DNA extraction using a traditional phenol/chloroform protocol, the use of SCAR multiplex PCR (one tube and two tube versions) and speciation using the morphometric tool COCCIMORPH for the first time with field samples.